ФУНКЦІОНУВАННЯ АСОЦІАТИВНОЇ СИСТЕМИ ДІАЗОТРОФИ-ОЗИМЕ ЖИТО ЗАЛЕЖНО ВІД СОРТОВИХ ОСОБЛИВОСТЕЙ РОСЛИН - Надкернична , О.В. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2008)
The associative nitrogen fixation of different winter rye sorts has been studied. It has been shown that such sorts as Charkovskoe 79, Struna, Novozibkovskoe 150, Borba, Verchniachskoe 32 have high N2- fixing potential. The mentioned sorts were noted by their high sensitivity to inoculation of nitrogen fixing bacteria from Azospirillum, Azotobacter, Bacillus, Pseudomonas genuses and ability to supply with effective functioning of N2-fixing bacteria – winter rye associative system.